1995
DOI: 10.1128/iai.63.9.3279-3286.1995
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant Salmonella typhimurium vaccine induces local immunity by four different routes of immunization

Abstract: Immunization of mice with an attenuated Salmonella typhimurium strain (Phop c) carrying a plasmid encoding a hybrid form of the hepatitis B virus core antigen (HBc) induced specific antibody responses against the bacterial lipopolysaccharide (LPS) and HBc. Different mucosal routes of immunization, i.e., oral, nasal, rectal, and vaginal, were compared for their ability to induce a systemic as well as a mucosal response at sites proximal or distant to the site of immunization. Anti-LPS and anti-HBc immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(92 citation statements)
references
References 22 publications
5
86
1
Order By: Relevance
“…(2) it avoids the denaturation of antigens in the stomach; (3) it can deliver two or more foreign antigens at the same time; (4) it induces both cell-mediated and humoral responses [17][18][19][20]24]. As an efficient live bacterial vector, attenuated S. typhimurium has been used to deliver H. pylori antigens, such as the urease A and B subunits, with promising protective results in animal models [21,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…(2) it avoids the denaturation of antigens in the stomach; (3) it can deliver two or more foreign antigens at the same time; (4) it induces both cell-mediated and humoral responses [17][18][19][20]24]. As an efficient live bacterial vector, attenuated S. typhimurium has been used to deliver H. pylori antigens, such as the urease A and B subunits, with promising protective results in animal models [21,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…Each symbol represents the mean number of spots from three mice, with the error calculated as S.E.M. rium carrying foreign antigens have been shown to be capable of inducing antibodies detectable in lung washes [27,28]. Walker et al [27] investigated responses after three immunisations and found detectable ASC numbers mainly after boosting, suggesting that multiple inoculations may be required for detectable responses, consistent with detection of lung ASC predominantly in boosted mice.…”
Section: Discussionmentioning
confidence: 98%
“…However, Seo et al (2010) have used eye drop immunization with an RASV to induce mucosal antibodies assayed in vaginal secretions and also induce protection to challenge with a wild-type virulent Salmonella enterica serovar Typhimurium strain. Previous work (Hopkins et al, 1995) had demonstrated that delivery of an RASV strain by diverse mucosal routes induced antibodies in distal mucosal sites, as well as in serum, except for rectal immunization, which only resulted in mucosal responses in the intestinal tract. In contrast, Kantele et al (1998) observed that rectal immunization of human volunteers with antityphoid vaccine strain Ty21a induced better mucosal immune responses in nasal and rectal secretions and tears than did oral administration, which induced better mucosal responses in saliva and vaginal secretions.…”
Section: Introductionmentioning
confidence: 99%